Maternal anaemia and maternal, fetal, and neonatal outcomes in a prospective cohort study in India and Pakistan. (24th January 2019) - Parks, S; Hoffman, MK; Goudar, SS; Patel, A; Saleem, S; Ali, SA; Goldenberg, RL; Hibberd, PL; Moore, J; Wallace, D; McClure, EM; Derman, RJ
Abstract : Objective: To describe the association of maternal anaemia with maternal, fetal, and neonatal outcomes. Design: Prospective cohort study. Setting: Rural India and Pakistan. Population: Pregnant women residing in the study catchment area. Methods: We performed an analysis of a prospective pregnancy registry in which haemoglobin is commonly obtained as well as maternal, fetal, and neonatal outcomes for 42 days post‐delivery. Women 40 years or older who delivered before 20 weeks or had a haemoglobin level of <3.0 g/dl were excluded. Our primary exposure was maternal anaemia, which was categorised in keeping with World Health Organization criteria based on a normal (≥11 g/dl), mild (>10–10.9 g/dl), moderate (7–9.9 g/dl) or severe (<7 g/dl). haemoglobin level. The primary maternal outcome was maternal death, the primary fetal outcome was stillbirth, and the primary neonatal outcome was neonatal mortality <28 days. Results: A total of 92 247 deliveries and 93 107 infants were included, of which 87.8% were born to mothers who were anaemic (mild 37.9%, moderate 49.1%, and severe 0.7%). Maternal mortality (number per 100 000) was not associated with anaemia: normal 124, mild 106, moderate 135, and severe 325 ( P  = 0.64). Fetal and neonatal mortality was associated with severe anaemia: stillbirth rate (n/1000)—normal 27.7, mild 25.8, moderate 30.1, and severe 90.9; P  < 0.0001; 28‐day neonatal mortality (n/1000)—normal 24.7, mild 22.9, moderate 28.1, and severe 72.6 ( P  < 0.0001). Severe maternal anaemia was also associated with low birthweight (<2500 and <1500 g), preterm birth, and postpartum haemorrhage. Conclusion: Severe maternal anaemia is associated with higher risks of poor maternal, fetal, and neonatal outcomes but other degrees of anaemia are not. Interventions directed at preventing severe anaemia in pregnant women should be considered. Tweetable abstract: Severe maternal anaemia is associated with adverse fetal and neonatal outcomes in low/middle‐income countries. Tweetable abstract: Severe maternal anaemia is associated with adverse fetal and neonatal outcomes in low/middle‐income countries.